PENGARUH MODEL PEMBELAJARAN HIGHER ORDER THINKING SKILLS TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI SISTEM PENCERNAAN MANUSIA DI KELAS X SMA NEGERI 2 HILIMEGAI - Halawa, Imani Kristiani (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2025)
This research was motivated by subject teachers, especially biology, not using higher order thinking skills learning models and resulting in students being less motivated to learn. This research aims to determine the effect of the HOTS learning model on students' critical thinking abilities on the human digestive system material in class X SMA Negeri 2 Hilimegai. The type of research is quantitative, descriptive in nature. The research population was class X students of SMA Negeri 2 Hilimegai, while the research sample was class This research data was analyzed using the normality test and hypothesis testing using the SPSS version 20 application. The results of this research were that the sig. sig.(2-tailed) is 0.042 < 0.05, it is known that t count is 2.48689 > t table 2.25183 for the use of the higher order thinking skills learning model, it is concluded that the data is normally distributed so that students have an interest in participating in learning activities through the higher order learning model order thinking skills. Suggestions for teachers, it is best to use higher order thinking skills learning models with different variations and for future researchers it is best to carry out this research with a wider scope.